Mortality of Bemisia tabaci biotype B (sternorrhyncha: aleyrodidae) adults by aliphatic and aromatic synthetic sucrose esters - Alves, Mariangela [UNESP]; Boscolo, Maurício [UNESP]; Fernandes, Odair Aparecido [UNESP]; Nunes, Maria Andréia [UNESP] (Brazilian Archives of Biology and Technology, 2008)
O biótipo B de B. tabaci Gennadius tem se destacado como uma praga-chave de diversas culturas. O controle químico tem sido a principal tática de controle utilizada, embora já se tenha observado redução na eficiência dos produtos devido ao desenvolvimento de resistência. Assim, o objetivo do presente trabalho foi avaliar o efeito de diversos ésteres de sacarose com grupos alifáticos ou aromáticos sobre adultos de mosca-branca. Butirato de sacarose, caprato, octanoato, palmitato, oleato, actaacetato, ftlato, benzoato e diacetato hexaisobutirato de sacarose foram testados. Soluções de éster de sacarose foram preparadas e aplicadas sobre adultos capturados em armadilhas adesivas utilizando Torre de Potter. Ésteres alifáticos de sacarose com longas cadeias foram mais efetivos contra mosca-branca e as maiores taxas de mortalidade foram obtidas com oleato e octanoato de sacarose. Uma vez que estes compostos são caracterizados como tensoativos, dodecilsulfato de sódio foi testado para comparação e não se observou qualquer efeito. Butirato de sacarose e outros poliésteres de sacarose alifáticos ou aromáticos foram praticamente inócuos para mosca-branca.

The B-strain of Bemisia tabaci Gennadius is a key pest of several crops and chemical control is the main control method used by growers, although reduction in efficacy due to insecticide resistance has already been reported. The aim of this work was to investigate the insecticidal effect of an array of synthetic sucrose esters with the aliphatic and aromatic groups on whitefly adults. Sucrose butyrate, caprate, octanoate, palmitate, oleate, octaacetate, phthalate, benzoate, and sucrose diacetate hexaisobutyrate were tested. The solutions were prepared and applied on the adults caught on yellow sticky traps using the Potter spray tower. Long-chains sucrose aliphatic esters were more effective against the silverleaf whiteflies and the highest mortality was obtained with sucrose oleate and sucrose octanoate. Since these compounds were tensoactive, sodium dodecylsulphate was also tested for the comparison but no effect was observed. Sucrose butyrate and other aliphatic and aromatic sucrose polyesters showed negligible effect on the silverleaf whiteflies.
Keywords: Sucroesters; silverleaf whitefly; pest control; Integrated pest management